Round Pegs Do Not Fit Square Holes: The Case of Doubling Marine Fishers Income - Dinesh Singh Naorem; N. Sivaramane; V.R. Kiresur; S.K. Pandey; I. Sivaraman; Neha W. Qureshi; M. Krishnan (Journal of Indian Fisheries Association, 2023)
India is now looking to double income of the farmers by 2022. The focus is on coming up with new strategies for doubling famers and ishers income and also crsytalzing ways and means to revitalize the agriculture sector including fisheries. The percentage contribution of marine fisheries sector to total fish production of India declined from 49.69 per cent in year 2000 to 33 per cent in 2016. Again, the income scenario of the marine fishers have not been too encouraging i.e. income distribution at sectoral level is skewed in favour of mechanized and motorized fishers. The paper examined the threshold limits of marine isheruies of the state of Maharashtra, classification of the diﬀerent resources groups into five criteria viz. abundant, non-abundant, declining, collapsed and depleted. Prices were also delated using fish price index of FAO (2001-02). Data were collected from CMFRI annual reports and handbook of fisheries statistics. The study has found that Maharashtra marine fisheries was already exploited. So doubling fishers income by increasing the production alone is not possible. The only way to improve the marine fishers income is to regulate and implement the code of conduct for responsible fisheries (FAO, 1995) strictly, enforce ban on purse seiners, strictly ban mechanized vessels in near shore waters, etc.